1995
DOI: 10.1016/0014-5793(94)01322-r
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase in human lymphomononuclear cells activated by synthetic peptides derived from extracellular matrix proteins

Abstract: Synthetic peptides with sequences present in extracellular matrix proteins are capable of causing the expression of the inducible form of nitric oxide synthase (iNOS), detected by immunocytochemistry, and the release of NO by human lymphomononuclear cells incubated in their presence. Active peptides are 15-mers containing a characteristic 2-6-11 motif in which the amino acid residue at position 2 is Leu, Ile, Val, Gly, Ala or Lys; the residue at position 6 is always Pro; and residue 11 is Glu or Asp. The induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
5
14
0
Order By: Relevance
“…When the peptide was omitted, nitrite/nitrate produced amounted only to 1.8 nmol. Similar results had been obtained with peptide Pa1 in previous work (12,25). The production of nitrite/nitrate in the presence of Pa2 markedly decreased (2.8 nmol per 10 5 cells) when 1 mM NMLA was present in the incubation medium.…”
Section: Resultssupporting
confidence: 89%
“…When the peptide was omitted, nitrite/nitrate produced amounted only to 1.8 nmol. Similar results had been obtained with peptide Pa1 in previous work (12,25). The production of nitrite/nitrate in the presence of Pa2 markedly decreased (2.8 nmol per 10 5 cells) when 1 mM NMLA was present in the incubation medium.…”
Section: Resultssupporting
confidence: 89%
“…The gp91phox induction by Pa, as here reported, is consistent with the immunomodulating properties already described for this peptide, such as the release of TNF␣ and IFN␥ (13,42), since it has been described that gp91phox expression is induced in cultured MO by stimulation with both cytokines (43,44). The cytotoxic activity (14) and iNOS expression (18) on CD16 positive mature cells induced by Pa also agree with the enhanced gp91phox expression. Finally, it is interesting to note that Pa does not induce a release of IL-4 (13,42), since it has been described that human MO cultured with GM-CSF and IL-4 differentiate to DCs without superoxide-generating ability.…”
Section: Differential Gene Expression In Human Monocytessupporting
confidence: 90%
“…We have previously described that certain pep-tides, sharing a common structural motif (11)(12)(13), induce MO activation and differentiation when added to peripheral blood mononuclear cells (PBMC). They are known to promote the secretion of monokynes, expression of inducible NO synthase (iNOS), (14) and the appearance of a DNase activity associated with granules on mature MO (15). Synthetic peptide Pa (NVL-GAPKKLNESQAV), used in this work, belongs to this group of compounds.…”
mentioning
confidence: 99%
“…Human mononuclear phagocytes can produce iNOS mRNA and protein and, despite that, their ability to generate NO is very low (10); NO production seems also to depend on the state of maturation of monocytes (19). We have already shown that immunomodulating peptides, capable of stimulating Th1 cells thus causing the release of IFNg and IL-2, induce the expression of iNOS and NO synthesis (14,8). Evidence here reported ( Figs.…”
Section: Resultssupporting
confidence: 59%
“…An extra valine residue was always added in the C-terminus for convenience of synthesis. The selection of those amino acid sequences was based on the the presence of a structural pattern, which has already been shown to confer on them immunomodulating properties, manifested as activation of monocytes and presentation on HLA-II to Th1 cells (8,14). The following peptides were used: SVTALP-SKGLEHLK (peptide P1, residues 237-250 in TSHR); CLCADPYELDDDGR (peptide P2, residues 823-836 in TPO); and QVDAQPLRPCELQR (peptide P3, residues 24-37 in Tg.…”
Section: Resultsmentioning
confidence: 99%